2011
DOI: 10.2903/j.efsa.2011.2322
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the public health risks of bacterial strains producing extended-spectrum β-lactamases and/or AmpC β-lactamases in food and food-producing animals

Abstract: The potential contribution of food-producing animals or foods to public health risks by ESBL and/or AmpCproducing bacteria is related to specific plasmid-mediated ESBL and/or AmpC genes encoded by a number of organisms. The predominant ESBL families encountered are CTX-M, TEM, and SHV; the predominant AmpCfamily is CMY. The most common genes associated with this resistance in animals are bla CTX-M-1 (the most commonly identified ESBL), and bla CTX-M-14 , followed by bla and bla Among the genes encoding AmpC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
92
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(99 citation statements)
references
References 284 publications
(530 reference statements)
6
92
0
1
Order By: Relevance
“…CMY-2 is the most common type of AmpC enzymes among Enterobacteriaceae in farm and companion animals, food products, as well as humans. Other types of AmpC beta-lactamases are scarcely reported (1,11). It has been suggested that poultry can be an important reservoir of CMY-2 AmpC beta-lactamases (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMY-2 is the most common type of AmpC enzymes among Enterobacteriaceae in farm and companion animals, food products, as well as humans. Other types of AmpC beta-lactamases are scarcely reported (1,11). It has been suggested that poultry can be an important reservoir of CMY-2 AmpC beta-lactamases (1).…”
Section: Discussionmentioning
confidence: 99%
“…The major mechanism conferring resistance to cephalosporins is mediated by extended-spectrum beta-lactamases (ESBLs) and AmpC beta-lactamases (1). Although plasmid-mediated quinolone resistance (PMQR) genes confer only a low level of resistance to fluoroquinolones and resistance is mainly caused by point mutations of the quinolone resistance-determining region (QRDR), coding for gyrase and topoisomerase (2), the interaction between mutations in the QRDR and PMQR genes leads to higher levels of resistance to fluoroquinolones (3).…”
mentioning
confidence: 99%
“…The emergence of this type of resistance is mainly linked to the spread of genes encoding extended-spectrum beta-lactamases (ESBLs) and/or transferable AmpC beta-lactamases (pAmpC) (5). Poultry, primarily broilers, have been suggested as a source for these types of genes and/or the resistant bacteria (6)(7)(8). In Sweden, broilers are rarely treated with antibiotics and no usage of cephalosporins was registered in 2010 (9).…”
mentioning
confidence: 99%
“…An increase in the zone diameter of 5 mm or more, when either of the antimicrobial agents was combined with clavulanic acid, was considered evidence of ESBL production [16] . Phenotypic detection of AmpC production was carried out by determination of resistance to cefoxitin and susceptibility to cefepime [16,17] . DNA was extracted by Roche High Pure PCR Template Preparation Kit (Roche, France), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%